2021
DOI: 10.1590/1806-9282.20201076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mediterranean diet in patients with chronic spontaneous urticaria

Abstract: OBJECTIVE: Patients with chronic spontaneous urticaria often want to be informed about dietary modifications. There have been many studies evaluating dietary approaches in chronic spontaneous urticaria. In this study, we aimed to investigate the relationship between adherence to the Mediterranean diet and chronic spontaneous urticaria. METHODS:In this cross-sectional case-control observational study, 100 patients (70 males and 30 females, mean age: 38.6±13.0 years) with chronic spontaneous urticaria and age-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a cross-sectional study by Chen et al, 26 a Mediterranean diet that reduced the risk of urticaria was found to reduce the abundance of the potentially harmful bacterium Intestinibacter. 27 Dietary habits and medical conditions affect the composition of the gut microbiota, reducing the amount of variation that can be accounted for by genetic methods. Owing to the lack of data, we were unable to determine whether genetic factors were related to the confounding variables in this study.…”
Section: F I G U R E 2 All Results Of Mendelian Randomization (Mr) An...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study by Chen et al, 26 a Mediterranean diet that reduced the risk of urticaria was found to reduce the abundance of the potentially harmful bacterium Intestinibacter. 27 Dietary habits and medical conditions affect the composition of the gut microbiota, reducing the amount of variation that can be accounted for by genetic methods. Owing to the lack of data, we were unable to determine whether genetic factors were related to the confounding variables in this study.…”
Section: F I G U R E 2 All Results Of Mendelian Randomization (Mr) An...mentioning
confidence: 99%
“…Intestinibacter may exacerbate urticaria by inducing hypersensitivity reactions through LPS production; however, further research on this potential mechanism is necessary. In a cross‐sectional study by Chen et al., 26 a Mediterranean diet that reduced the risk of urticaria was found to reduce the abundance of the potentially harmful bacterium Intestinibacter 27 …”
Section: Discussionmentioning
confidence: 99%
“…The urticaria activity score in CSU patients over 7 days was inversely associated with the Mediterranean diet score, while the urticaria control test score was positively correlated. 113 The study suggests that the Mediterranean diet’s anti-inflammatory and antioxidant properties may help alleviate systemic inflammation and oxidative stress, 114 which contribute to the pathogenesis of CSU disease. In addition, adherence to the Mediterranean diet is linked to the restoration of balanced gut microbiota, with increases observed in Bacteroidetes and specific beneficial Clostridium groups, while decreases are noted in Proteobacteria and Bacillaceae phyla.…”
Section: Approaches Targeting Gut Microbiome For Cu Therapymentioning
confidence: 99%